1993
DOI: 10.3354/meps092135
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, nitrogen, and phosphorus leaching rates from Spartina alterniflora salt marshes

Abstract: Annual carbon, nitrogen, and phosphorus leachate rates from live Spartina alterniflora Loisel in a Louisiana (USA) salt marsh were estimated to be 200, 14, and 3 g m-2, respectively, and to peak in summer and higher salinit~es. Leachate losses of P, N and C are equivalent to a turnover of live plant tissues of 10, 17 and 49 d, respectively, when submerged, and 148, 250 and 721 d, respectively, when unsubmerged. Plant leachate losses during marsh submergence and non-submergence are nearly equal because release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 29 publications
0
34
0
3
Order By: Relevance
“…From our biomass harvests, seasonal and species-specific percent carbon data, and an annual live biomass turnover of 2.24 yr-' (Wohlgemuth 1988), we calculated aboveground productivities using the peak biomass (845 g C m-2 yr-l) and Smalley methods (776 g C m-' yr-L). Combined with Turner's (1993) data, we estimated a leaching rate of 41 to 85 g C m-2 yr-' (F = 62 g C m-' yr-').…”
Section: Macrophyte Carbon Budgetmentioning
confidence: 99%
See 2 more Smart Citations
“…From our biomass harvests, seasonal and species-specific percent carbon data, and an annual live biomass turnover of 2.24 yr-' (Wohlgemuth 1988), we calculated aboveground productivities using the peak biomass (845 g C m-2 yr-l) and Smalley methods (776 g C m-' yr-L). Combined with Turner's (1993) data, we estimated a leaching rate of 41 to 85 g C m-2 yr-' (F = 62 g C m-' yr-').…”
Section: Macrophyte Carbon Budgetmentioning
confidence: 99%
“…Leaching of DOC from plant tissues can occur both during tidal submergence and aerial exposure (Gallagher et al 1976, Turner 1978, Pakulski 1986, Moran & Hodson 1990, Turner 1993, Mann & Wetzel 1996. Table 3.…”
Section: Macrophyte Carbon Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the decomposition of vascular salt marsh plant tissues tends to contribute more refractory humic-like components which make up of 66% of the total dissolved humic substance (Moran and Hodson, 1994). In addition, previous studies suggested that carbon leaching rate of Spartina alterniflora salt marshes reached peak during summer (Turner, 1993), which could explain the salt marsh export observed during August 2010 to be more significant than March 2011 and 2012. Our EEM-PARAFAC studies on the leached DOM confirm that plant leachates indeed produced more of the protein-like C3 relative to humic-like components.…”
Section: Sources and Reactivity Of The Parafac Componentsmentioning
confidence: 99%
“…However, from a quantitative perspective, the significance of leachate export relative to in situ DOM production may vary in different ecosystems (Turner, 1993) and thus the accumulation, dynamics and fate of salt marsh exported DOM remains difficult to constrain.…”
Section: Introductionmentioning
confidence: 99%